The witches - Dahl, Roald; Blake, Quentin (New York Scholastic, 1997)
A young boy and his Norwegian grandmother, who is an expert on witches, together foil a witches' plot to destroy the world's children by turning them into mice.
UCWS-2014-G-1859 donated by Prof. Eric Julian Manalastas
Keywords: Witches -- Fiction; Grandmothers -- Fiction